Distinctive mitogenomic lineages within populations of White-tailed Eagles. Issue 2 (22nd December 2021) - Hansen, Charles Christian Riis; Baleka, Sina; Guðjónsdóttir, Sólveig Magnea; Rasmussen, Jacob Agerbo; Ballesteros, Jesus Adrian Chimal; Hallgrimsson, Gunnar Thor; Stefansson, Robert A; von Schmalensee, Menja; Skarphédinsson, Kristinn Haukur; Labansen, Aili Lage; Leivits, Madis; Skelmose, Kim; et al.
Abstract: Using whole mitochondrial DNA sequences from 89 White-tailed Eagles ( Haliaeetus albicilla ) sampled from Iceland, Greenland, Norway, Denmark and Estonia between 1990 and 2018, we investigate the mitogenomic variation within and between countries. We show that there is a substantial population differentiation between the countries, reflecting similar major phylogeographic patterns obtained previously for the control region of the mitochondria, which suggested two main refugia during the last glacial period. Distinct mitogenomic lineages are observed within countries with divergence times exceeding the end of the last glacial period of the Ice Age. Deviations from neutrality indicate that these lineages have been maintained by natural selection and there is an excess of segregating amino acids in comparison with number of fixations suggesting a large load of deleterious mutations. The maintenance of the distinct mitogenic lineages within countries inflates our estimates of divergence times. Lay Summary: Whole mitochondrial genomes were used to examine the population genetics of White-tailed Eagles. Large genetic differences potentially upheld by selection within populations were identified. Potential time of population splits during the last Ice age were identified. Graphical Abstract: